Age and structural lag : society's failure to provide meaningful opportunities in work, family, and leisure - Riley, Matilda White, 1911-; Foner, Anne.; Kahn, Robert Louis, 1918- (New York : Wiley, 1994)
"In twentieth-century industrial societies most of us live longer and healthier lives than ever before in history. Yet the social structures and institutions that provide opportunities for our lives are still marked by age constraints that were appropriate a century ago. Education is still primarily reserved for the young; work and family responsibilities are crowded into the middle years; while leisure and free time are allocated to the added decades of retirement. Even the many vital men and women past age 65, or even 55, who want or need paid jobs are regarded as "too old" to work. Lives have changed, but social structures have not caught up. There is a lag or mismatch between lives and structures." "What are the detrimental consequences of this structural lag for individuals and society at large? How do structures change, and how can they be changed to enhance lives at every age? What alternative structures would lessen the burdens of middle age, prepare children for the complexities of the real world, and provide opportunities for productivity, independence, and esteem for older people?" "Seeking answers to such questions, the twelve chapters in this book bring powerful insights to bear on structural lag from sociology and psychology; and they draw upon history, anthropology, and economics to disclose new perspectives on the past and the present, and new hope for the future. While special attention is paid to structures affecting the old, issues relating to all ages are explored in respect to work, family, education, retirement, and other domains of social life." "This is a powerful book, revolutionary in its conceptions and implications, calling for structural changes in society; a new mix of work, family, and leisure. Opening a critical but neglected area, it is the first book publication of a long-range Program on Age and Structural Change (PASC) directed by Matilda White Riley at the National Institute on Aging and involving an international network of scholars." "Timely, authoritative, and the only book to offer a comprehensive treatment of this increasingly important social problem, Age and Structural Lag is a valuable resource for psychologists, sociologists, and those interested in human development and aging; for those in professional practice and in policy, both public and private; and for sophisticated readers concerned with major issues of everyday life."--BOOK JACKET.."--BOOK J
11. Changing Policy Signals / Richard V. Burkhauser and Joseph F. Quinn -- 12. Endnote: The Reach of an Idea / Anne Foner.
"A Wiley-Interscience Publication."
Includes bibliographical references and indexes.
Keywords: Social change -- United States; Social structure -- United States; Aging -- Social aspects -- United States; Age and employment -- United States